Introducción a la investigación contable en Brasil (2018)
The objective of this paper is to present the current structure of accounting research in Brazil, with emphasis on three indexed events, the 35 accounting journals and the role of masters and doctorates. For this purpose, a content analysis was carried out, based on a systematic review of the literature published in the main Brazilian accounting journals between 2008 and 2013. Among the findings, the characteristics of accounting as a scientific field in Brazil, authors, evolution of the lines of research and evolution of the journals are highlighted. The recent structure of accounting research in Brazil, sponsored by the Ministry of Education and the requirements of Capes, makes it a mature model of accounting research in Latin America.